Exploring the Impact of Country of Origin on Turkish Consumer Perceptions in the Automotive Industry - Buğur, Ozan (2024)
The extensive network of research on the influence of Country of Origin (COO) and Country of Manufacturing (COM) has covered various product groups, yet its focus on the Turkish automotive industry and consumers remains to be accomplished. This research provides a literature background enriched with contemporary perspectives on Turkey’s automotive industry and the aspects of Turkish consumer behaviour. Through a quantitative approach employing a questionnaire, it investigates the extent to which COO and COM shape Turkish car buyers' evaluations, particularly concerning pricing and quality perceptions. Additionally, the study explores the relationship of COO and COM with sociocultural factors such as social class, nationalism, ethnocentrism, avoidance, and skepticism. In summary, this study provides an insightful contribution to future literature and management practices.